Oncologic outcomes of human papillomavirus–associated oropharynx carcinoma treated with surgery alone: A 12‐institution study of 344 patients. Issue 17 (6th May 2021) - Ryan, William R.; Xu, Mary J.; Ochoa, Edgar; Plonowska‐Hirschfeld, Karolina A.; Zebolsky, Aaron L.; Ha, Patrick K.; Bewley, Arnaud F.; Mallen‐St. Clair, Jonathan; Joshi, Arjun S.; Coffey, Charles S.; Faraji, Farhoud; MacDonald, Bridget V.; et al.
Abstract : Background: The oncologic outcomes of surgery alone for patients with American Joint Committee on Cancer 7th edition (AJCC 7th) pN2a and pN2b human papillomavirus–associated oropharynx squamous cell carcinoma (HPV+OPSCC) are not clear. Methods: The authors performed a 12‐institution retrospective study of 344 consecutive patients with HPV+OPSCC (AJCC 7th pT0‐3 N3 M0) treated with surgery alone with 6 months or more of follow‐up using univariate and multivariate analyses. Results: The 2‐year outcomes for the entire cohort were 91% (182 of 200) disease‐free survival (DFS), 100% (200 of 200) disease‐specific survival (DSS), and 98% (200 of 204) overall survival (OS). The 18 recurrences within 2 years were 88.9% (16 of 18) local and/or regional recurrences and 11.1% (2 of 18) distant metastases. Recurrences were not significantly associated with smoking, pT stage, or pN stage. The 16 patients with locoregional recurrences within 2 years all underwent successful salvage treatments (median follow‐up after salvage: 13.1 months), 43.8% (7 of 16) of whom underwent salvage surgery alone for a 2‐year overall salvage radiation need of 4.5% (9 of 200). The 2‐year outcomes for the 59 evaluable patients among the 109 AJCC 7th pT0‐2 N2a‐N2b patients with 1 to 3 pathologic lymph nodes (LNs) were as follows: local recurrence, 3.4% (2 of 59); regional recurrence, 8.4% (5 of 59); distant metastases, 0%; DFS, 88.1% (52 of 59); DSS, 100% (59 of 59); OS, 96.7% (59 of 61); and salvage radiation, 5.1% (3 of 59). Conclusions: With careful selection, surgery alone for AJCC 7th pT0‐T2N0‐N2b HPV+OPSCC with zero to 3 pathologic LNs without perineural invasion, extranodal extension, or positive margins results in high DFS, DSS, OS, and salvage treatment success. Because of the short‐term follow‐up, these data support further investigation of treatment de‐escalation in this population. Abstract : With careful selection, surgery alone for human papillomavirus–associated oropharynx squamous cell carcinoma, American Joint Committee on Cancer 7th edition pT0‐2, N2a‐N2b with 1 to 3 pathologic lymph nodes without perineural invasion, extranodal extension, or positive margins can result in favorable disease‐free survival, disease‐specific survival, overall survival, and salvage treatment success rates.